Social and cultural capital and learners’ cognitive ability: issues and prospects for educational relevance, access and equity towards digital communication in China - Kai, Wang (Current psychology (New Brunswick, N.J.), 2023)
Past researchers examined how an individual’s social as well as cultural exposure and experiences impact the educational excellence of a learner towards global digital communication. It is essential to recognize the structural relationship of educational institutions as they seem to influence the learner’s education learning outcome in the context of digitizing the global communication. Hence, this research study investigates the relationship between social and cultural capital orientation of the learners, learner’s cognitive ability, and learner’s family roots. For this, the study adopts descriptive correlational research design which identifies, describes, and explains the natural relationships between the variables. The study uses the following instruments to gather the data from 387 respondents: the Social and Cultural Capital Questionnaire (SCCQ) and the Otis-Lennon Scholastic Ability tests (OLSAT). The research subjects of the study are college graduate students selected from Universities in China. With literacy as the highest factor, the study found that the participants demonstrate higher levels of social and cultural capital orientation. Further, the participant’s cognitive ability is found to be mediocre. It was also observed that participant’s parent’s education influenced learner’s educational achievements in terms of cultural and social competence. Likewise, the study found that global social-cultural competence and literary practices are related to learner’s cognitive level. In addition, family income is identified as the variable that affects learner’s cognitive ability as well as social-cultural orientation. Finally, the study discusses the implications and proposed suggestions for future research.